Characterisation of Diamond-Like Carbon (DLC) laser targets by Raman spectroscopy. (April 2016) - Haddock, D.; Parker, T; Spindloe, C; Tolley, M
Abstract: The search for target materials suitable for High Power Laser Experiments at ultralow thicknesses (below ten nanometres) is ongoing. Diamond-Like Carbon is investigated as an answer for a low-Z material that can survive target chamber pump-down and laser prepulse. DLC was produced using Plasma-Enhanced Chemical Vapour Deposition, using with varying gas flow mixtures of argon and methane. The methane plasma deposits amorphous carbon onto the substrate and the argon plasma re-sputters the weakly bonded carbon leaving a high proportion of diamond-like bonding. Bonding natures were probed using Raman spectroscopy; analysis of the resulting spectrum showed that flow rates of 40sccm/60sccm methane to argon produced DLC films with a diamond-like ( sp 3 ) content of ∼20%. Increasing the methane gas flow decreased this value to less than 5%. DLC foils were processed into laser targets by method of float off; using a sodium chloride release layer and lowering into water, this was then lifted onto an array of apertures allowing for laser irradiation of the material with no backing. DLC with 20% sp 3 content showed superior yield when compared to other materials such as metals and some plastics of the same thickness, with ∼70% of the target positions surviving the float off procedure at <10nm. As a result of this work DLC targets have been available for a number of experiments at the Central Laser Facility.